LY-CoV1404 (bebtelovimab) potently neutralizes SARS-CoV-2 variants - Westendorf, Kathryn; Žentelis, Stefanie; Wang, Lingshu; Foster, Denisa; Vaillancourt, Peter; Wiggin, Matthew; Lovett, Erica; van der Lee, Robin; Hendle, Jörg; Pustilnik, Anna; Sauder, J. Michael; Kraft, Lucas; et al. (Cell reports (Cambridge), 2022)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)-neutralizing monoclonal antibodies (mAbs) can reduce the risk of hospitalization from coronavirus disease 2019 (COVID-19) when administered early. However, SARS-CoV-2 variants of concern (VOCs) have negatively affected therapeutic use of some authorized mAbs. Using a high-throughput B cell screening pipeline, we isolated LY-CoV1404 (bebtelovimab), a highly potent SARS-CoV-2 spike glycoprotein receptor binding domain (RBD)-specific antibody. LY-CoV1404 potently neutralizes authentic SARS-CoV-2, B.1.1.7, B.1.351, and B.1.617.2. In pseudovirus neutralization studies, LY-CoV1404 potently neutralizes variants, including B.1.1.7, B.1.351, B.1.617.2, B.1.427/B.1.429, P.1, B.1.526, B.1.1.529, and the BA.2 subvariant. Structural analysis reveals that the contact residues of the LY-CoV1404 epitope are highly conserved, except for N439 and N501. The binding and neutralizing activity of LY-CoV1404 is unaffected by the most common mutations at these positions (N439K and N501Y). The broad and potent neutralization activity and the relatively conserved epitope suggest that LY-CoV1404 has the potential to be an effective therapeutic agent to treat all known variants. [Display omitted] •LY-CoV1404 potently neutralizes SARS-CoV-2 Omicron, BA.2 Omicron, and Delta variants•No loss of potency against currently circulating variants•Binding epitope on RBD of SARS-CoV-2 is rarely mutated based on current GISAID data•Breadth of neutralizing activity and potency supports clinical development Westendorf et al. show that LY-CoV1404 is a potent SARS-CoV-2-binding antibody that neutralizes all known variants of concern and that its epitope is rarely mutated.